Genotyping of Staphylococcus aureus isolated from humans, bovine subclinical mastitis and food samples in Argentina - Reinoso, Elina Beatríz (2008)
The aim of the present study was to characterize genotypically 45 Staphylococcus aureus strains isolated from humans, bovine subclinical mastitis and food samples in Argentina by rep-PCR and PCR amplification of virulence genes. Resistances to various antibiotics could be observed for the human S. aureus, less pronounced for the bovine strains, but not for the eight S. aureus isolated from food samples. The strains could be classified genotypically by rep-PCR and by amplification of the genes encoding protein A, coagulase, clumping factor, the collagen adhesin domains A and B, capsular polysaccharide 5 and 8, the accessory gene regulator agr classes I to III, and the S. aureus gene regulator sae. rep-PCR analyses and the different gene patterns revealed that the strains could be divided into seven groups mostly matching with the origin of the isolates. The present study describes genotypic variations of S. aureus strains isolated from different origins in Argentina. The study provides a valuable insight into molecular specificities of this important pathogen.